Analisis Ketebalan Dan Kepadatan Aspal Terhadap Hasil Core Drill Pada Pekerjaan Lapis Permukaan AC-WC (Asphalt Concrete – Wearing Course) - Nurul Insani Suhardi; Abdul Rahim Nurdin; Tamrin Mallawangeng (Program Studi Teknik Sipil Universitas Bosowa, 2026)
The design of asphalt mixtures in Indonesia generally employs the conventional Marshall method, with a compaction of 2x75 blows for heavy traffic and an air void limit of 3%-5%. To assess field compaction, a Core Drill Test is performed using a heavy Tandem Roller, with 18 passes conducted in this study. The research aims to compare the density of the AC-WC surface layer used in the laboratory and in the field, as well as to analyze the thickness and density test results of the AC-WC surface layer according to specifications. The test results showed a slight difference between field density (2.25 g/cc) and laboratory density (2.27 g/cc), with a difference of 0.02 g/cc, which is considered nearly equivalent. However, this density variation should be noted as it can affect the load-bearing capacity and durability of the pavement layer. From STA 2+800 to 3+000, all samples' thickness and density met the specifications. Although this difference does not align with the asphalt mixture design (JMF), it falls within the tolerances specified in the 2018 Revision 2 Bina Marga standards, indicating that the differences in thickness and density are still acceptable.